THE PROBLEM OF FORMATION OF COMMUNICATIVE CULTURE OF INDIVIDUAL IN TERMS OF COMPUTERIZATION OF SOCIETY - Kovtun, O. (Journal of Information Technologies in Education (ITE), 2016)
In the article is considered the problem and revealed the foundations of communicative culture of personality, that appears as a certain degree of social and communicational properties unity of human, and is found in its ability to solve the problem of life and production, build interpersonal relationships at various levels to implement adequate self-realization and adaptation in modern society. At the present stage of formation and development the competitive society the main condition is providing people with education of high-quality. Ukraine must ensure making positive changes in the educational system that Ukrainian teachers to be high valued on the world labor market. The tendency to growth of the society order on preparation the high-qualified specialists for different branches of national economics is identified. The concept "culture" is reviewed as a set of social norms and values in the context of personal phenomena in the scientific literature. Communication and culture are compared as two important interrelated aspects of human social existence. Such aspects of communication as interactions, relationships, contacts, exchanges are revealed. It is determined that the communicative culture of personality is an important component of personal culture and appears as a condition of personal fulfillment. Therefore, it can be considered as a complex psychological new formation of personality, the result of its social and communicative development. The process of integrating of communicative and creative components in the structure of self- consciousness of individual that actualizes creative communication of personality. It was found that the reaction on the behavior of others in the process of communication is always mediated by self-consciousness that is related to its reflective "I". An important role in the implementation of communicative and creative components plays an emotional component of communication, the components of it are empathy, spontaneity, respect for others, honesty, openness to environment. Analysed the concept of three-subject didactic. In the research is analyzed educational systems that are actively involved in formation the communicative culture of personality. Taken into account innovative approach of Makarenko to the formation of communicative abilities of pupils. The educational system of V. O. Sukhomlynskyi where the teacher should focus on the social interaction as the main mechanism of development the communication skills of students is studied. Explored the phenomenon of sensitive phases of human development as an important aspect of formation the communicative culture. The role socialization theory of psycho-pedagogical paradigm of formation the communicative culture of students is considered. It was found that identification with a particular social role has negative consequences for the development and formation of personality. It is shown that the rate of communicative culture of human is its attitude to others, verbal and nonverbal speech, human behavior that becomes external manifestation of emotional moods, properties of character and the reflection of human's attitude to the events,surrounding world and other business relationships.